(untitled) (European journal of volunteering and community-based projects, 2022)
With "Reform of the Third Sector" it indicates the set of rules that has rearranged the non-profit and social enterprise. To date, the legislative intervention has not yet been completed, as the acts foreseen by the legislative decrees implementing the delegated law n.106 of 2016 are being implemented. Each institution will have to evaluate whether or not to register in the National Register of Third Sector entities, as well as from the specific section of the same in which it will be placed. An assessment that will strongly affect the purposes of each individual subject and substantially on the everyday organization and on the way of understanding and making non-profit. The change will be above all cultural, social, participatory and democratic, in associative practices and, in governance. This contribution, starting from a regulatory analysis, aims to assess the fiscal implications that non-profit entities will have to face in the coming months, weighing consciously the approach to the new legislation. For those who will not be part of the Third Sector Entities and who will not apply the forecasts contained in Legislative Decree No. 117/2017, it is necessary to understand what will be, to reform definitively in force, the fiscal provisions concretely applicable. More in detail you will see how the same D.Lgs. 117/2017 brings significant changes for those who will remain out of the reform.